What Determines The Capital Structure of Property, Real Estate and Building Construction Companies? Evidence from Indonesian Listed Companies - Fatimah, Sari Fitri; Witiastuti, Rini Setyo (Management Analysis Journal, 2020)
This research is intended to prove the influence of financial flexibility, asset structure, firm size, profitability and business risk on the capital structure. The population on this study are property, real estate and building construction sector that are listed on the Indonesia Stock Exchange in 2009-2018. The number of samples used were 28 companies with a purposive sampling method. The data studied was obtained from the Indonesia Stock Exchange (IDX). Methods of data analysis used in this study is multiple linear regression. The results showed that financial flexibility has not significant negative effect on capital structure. Asset structure and firm size have a significant positive effect on capital structure. The profitability and business risk have a significant negative effect on capital structure. Further research is needed to use another proxies such as ROE for profitability variables or standard deviations from ROE for business risk on capital structure and add another sectors or the number of observation periods.